Les enjeux de l'enseignement pour les professeurs d'université au Québec - Frédéric Deschenaux (Nantes Université, 2013)
In Quebec, the task of university professors must be shared between the three main components that are teaching, research and service to the community. However, all these tasks are not of equal value in the eyes of teachers in a context where research is highly valued. While the relationship with students is a tangible source of job satisfaction for teachers, even the most satisfying aspect of their work, it appears that the teaching generating stressful situations and anxiety, sometimes leading to burnout. The qualitative analysis of an open question (768 answers collected by an online survey) allows to infer three issues of concern to teachers about the university: 1 - the imbalance between tasks, 2 - threats to the quality of education and 3 - the relationship to knowledge of students. These elements lead to question the "idea of ​​a university" advocated by teachers Quebec as the transmission of knowledge in the university.